Sorption-desorption mechanisms of imazapic and imazapyr herbicides on biochars produced from agricultural wastes - Yavari, S. (Elsevier Ltd, 2016)
Interest in biochar application as soil amendment for mitigation of environmental contaminants is increasing considerably. However, there is still limited knowledge on how biochar influences immobilization of polar pesticides in agricultural soils. In this study, sorption and desorption of two polar persistent herbicides, imazapic and imazapyr, were evaluated in a rice field soil amended with oil palm empty fruit bunches (EFB) and rice husk (RH) biochars produced in different temperatures. The obtained results indicate that addition of biochars to the soils (1 (w/w)) could enhance both herbicides sorption. The extent of the effects, however, was found to be different in various biochars and herbicides. The biochars derived from EFB showed higher capabilities in sorption of both herbicides rather than RH biochars. The importance of pyrolysis temperature was determined based on the resultant biochar functionality. The outcomes of biochars elemental analyses, cation exchange capacity (CEC) values and fourier transform infrared spectroscopy (FTIR) spectra indicate that lower conversion temperature (300 °C) increases materials surface functional groups. Therefore, low temperature biochars were found to be more efficient in sorption of polar molecules. The EFB biochars produced in 300 °C was the most effective biochar which enhanced the sorption of imazapic and imazapyr up to 59.90 and 69.94, respectively. It can be concluded that the biochars sorption properties were directly controlled by production variables (feedstock kind and pyrolysis temperature) and the sorption mechanisms were determined based on the physicochemical characteristics (polarity, hydrophilicity and ionizability) of the sorbate molecules. © 2016 Elsevier Ltd. All rights reserved.